TAʼLIM JARAYONLARNI KUZATISH VA OʻZLASHTIRISH IMKONINI BERUVCHI TEXNOLOGIYALARDAN FOYDALANISH - Matnazarov, J. (SCIENCE and SOCIETY, 2024)
The article analyzes risks in creating individualized learning trajectories for students, core competencies, Internet of Things (IoT), social media integration, collaborative learning, artificial intelligence, personalized learning paths.